Laparoscopic TAPP repair following tumescent injection: The patient outcomes and feasibility for surgeons - Abdul Rehman Alvi, Farhan Tahir, Said Umer, Amin Warraich, Ahsan Rehman, Mobeen Adnan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laparoscopic transabdominal preperitoneal inguinal hernia repair (TAPP) is technically demanding procedure with relatively long learning curve. Procedure is associated with operative and postoperative complications and pain, especially when performed by inexperienced surgeon. Most of the problems are associated with different anatomical environment and technical inadequacy. In order to make TAPP relatively simple with better visibility of landmarks, we used pre peritoneal infiltration of 60-100ml saline with lidocaine and epinephrine before proceeding for TAPP repair. Methods: About 60-100 ml of diluted lidocaine with epinephrine solution was injected in pre peritoneal space below arcuate line and extending to and around hernial sac. Care is taken not to inject in triangle of doom. Laparoscopic aspiration needle was used for injection after lifting peritoneum with grasper. Tumescent TAPP was performed in 35 patients (32 men, 3 women; mean age, 44.3 years). Results: With use of tumescent TAPP, it was relatively simple to identify anatomical landmarks owing to bloodless field. One of the main advantages was demonstration of procedure to residents leading to better understanding and more confident dissection while being performed under supervision. The mean operation time was 95 min. ranging from 55 to 110 minutes. Another advantage was reduced pain in early post-operative period. Conclusions: Tumescent injection before TAPP is easier and safe with advantage of clearer anatomy and reduced post-operative pain.